2020
DOI: 10.7554/elife.55275
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics at the serine loop underlie differential affinity of cryptochromes for CLOCK:BMAL1 to control circadian timing

Abstract: Mammalian circadian rhythms are generated by a transcription-based feedback loop in which CLOCK:BMAL1 drives transcription of its repressors (PER1/2, CRY1/2), which ultimately interact with CLOCK:BMAL1 to close the feedback loop with ~24 hr periodicity. Here we pinpoint a key difference between CRY1 and CRY2 that underlies their differential strengths as transcriptional repressors. Both cryptochromes bind the BMAL1 transactivation domain similarly to sequester it from coactivators and repress CLOCK:BMAL1 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 71 publications
5
74
0
Order By: Relevance
“…To understand the dramatic change in the function of CRY1 upon Arg293 to His293 mutation and to assess the role of Arg293 in CRY1, we employed molecular dynamics simulations. Computational analysis suggested that Arg293 might be a critical residue for the regulation of the serine loop in CRY1 which is known to be important for CLOCK binding to the secondary pocket (38). Replacing Arg293 with His changes a highly dynamic serine loop into a less dynamic state and closes the gate of the secondary pocket ( Figure 5B-E), which may be responsible for the reduced binding of CLOCK to the mutant CRY1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To understand the dramatic change in the function of CRY1 upon Arg293 to His293 mutation and to assess the role of Arg293 in CRY1, we employed molecular dynamics simulations. Computational analysis suggested that Arg293 might be a critical residue for the regulation of the serine loop in CRY1 which is known to be important for CLOCK binding to the secondary pocket (38). Replacing Arg293 with His changes a highly dynamic serine loop into a less dynamic state and closes the gate of the secondary pocket ( Figure 5B-E), which may be responsible for the reduced binding of CLOCK to the mutant CRY1.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction allows the serine loop, located adjacent to the secondary pocket, to adapt different conformations. A recent study indicates that PER2 remodels the serine loop of CRY2 and, in turn, enhances its affinity towards BMAL1/CLOCK (38). In the same study, replacement of amino acid residues in the serine loop of CRY1 reduces its affinity to BMAL1/CLOCK.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Kd should be at least on the order of 0.1. In fact, Fribourgh et al(41), who recently studied the docking of PER2:CRY1/2 to the core PAS domain of BMAL:CLOCK, measured Kd ≈ 400 nM, or in dimensionless terms, Kd ≈ 40. This estimate may easily be off by a factor of 10, because the measurements were made in vitro with purified protein domains (not with full length proteins).…”
mentioning
confidence: 99%